Effects of cotton spacing on insect infestation, natural enemies and yield, Gezira State, Sudan - Hassan, A.E.M; Salih, S.O. Salih; Alloub, H.E (المجلة الزراعية; مجلد 16 عدد 1 (2018), 2018)
In the Gezira Scheme, Sudan, cotton ( Gossypium barbadense L.) has been grown under irrigation without insecticidal use for more than 30 years (1911-1945). That was probably due to the traditional growing of cotton, in the same area, under rainfed before the establishment of the Gezira Scheme.  Such practice witnessed a balanced agricultural ecological system in the cotton growing area. Since season 1945/46 till now, more than 300 insecticides and insecticide mixtures were recommended. The average yield was less than 7 kantar/feddan for upland cotton. The objective of this study was to test the effect of spacing on insect infestation, natural enemies and yield of Brazilian (LL) cotton cultivar enemies without insecticidal spraying. The crop was planted in June 20, 2012 at intra-row spacing of 10 cm, 20 cm, 30 cm and 40 cm and 50 cm with 4-6 seeds/hole and then thinned to three plants per hole, on 80 cm ridges. Insect pests and natural enemies were monitored. Results showed that the sucking insects, Jassid ( Jacobiassica lybica ) and the whitefly ( Bemisia tabaci ) appeared in July, increased in number to reach the peak in August and then decreased in October. The Brazilian (LL) cultivar was attacked by the bollworms, Helicoverpa armigera and Earias insulana . Shedding of reproductive structures due to bollworms was recorded. H. armigera resulted in higher damage of reproductive structures during August in the wider spacing (50 cm) while, the damage was lower during September. For E. insulana , damage of reproductive structures was lower in the wider spacing compared to narrow spacing during August and September. Natural shedding of reproductive structures was low during August and high during September in the widest spacing (50 m). The buildup of natural enemies started in July to reach the peak in September and decreased in October, in a density dependent pattern with sucking insect pest populations. The yield of cotton in kantar per hectare was 29.8 at 10 cm spacing (5 folds) and 14.8 at 20 cm (2.5 folds) as compared to 6 at 50 cm the recommended spacing. However, the quality, in term of stickiness, was satisfactory among all spacing under test. The study revealed that narrow spacing reflected higher yield with good quality of cotton. It is recommended to grow the Brazilian LL cotton cultivar at a spacing of 10 cm for higher yield and best quality. استمرت زراعة القطن طويل التيلة بالري الصناعي بمشروع الجزيرة بالسودان لأكثر من ثلاثين عاماً دون رش المبيدات لحماية المحصول من الآفات (1911-1945). يُعزى ذلك لزراعة القطن قصير التيلة بالأمطار ولمدة طويلة سبقت قيام المشروع. تمخض عن هذه الممارسة توازن إيكولوجي في بيئة المشروع. ومنذ  أن بدأ إدخال المبيدات لمكافحة الآفات في الموسم 1946/1945، حتى الآن تمت إجازة أكثر من 300 من المبيدات ومخاليط  المبيدات. عليه الهدف من هذه الدراسة معرفة أثر الزراعة المبكرة في مسافات متباينة على كمية ونوعية القطن المنتج. تمت زراعة القطن في 20 يونيو 2012 وعلى مسافات 10 سم،       20 سم ، 30 سم و 40 سم بين النباتات  وتمت مقارنتها مع المسافة المعيارية 50 سم و ذلك بزراعة 3 بذور في كل حفرة. تم رصد الآفات الحشرية والأعداء الطبيعية. أظهرت النتائج أن الحشرات الماصة، النطاط الأخضر ( Jacobiasca lybica) والذبابة البيضاء ( Bemisia tabaci ) بدأتا في الظهور في شهر يوليو ووصلتا قمة التواجد في أغسطس وبدأتا في الانحسار في أكتوبر. اتضح أن الصنف تحت الاختبار  (Brazillian LL)يصاب بديدان اللوز الأفريقية ( Helicoverpa armigera ) والمصرية ( Earias insulana ). تساقط الأزهار واللوز reproductive structures)) قد دون.  التساقط نسبة للإصابة بدودة اللوز الأفريقية كان كبيراً في أغسطس في المسافات 40 سم و50 سم بينما انخفض خلال سبتمبر. بالنسبة لديدان اللوز المصرية الإصابة على الأزهار واللوز كانت قليلة على المسافات الواسعة مقارنة بالإصابة على المسافات الضيقة  خلال شهري أغسطس وسبتمبر. أما التساقط الطبيعي لهذه المكونات فقد كان قليلاً في أغسطس وكثيراً في سبتمبر عند المسافة 50 سم. زيادة الأعداء الطبيعية بدأت في يوليو ووصلت قمتها في سبتمبر ثم انحسرت في أكتوبر بمنوال الكثافة غير المستقلة عن عشائر الآفات الماصة. إنتاجية القطن بالقنطار للفدان 29.8 (5 أضعاف) للمسافات البينية 10سم و 14.8 (2.5 ضعف) للمسافات البينية 20 سم مقارنة بالمسافة البينية 50سم. نوعية القطن المنتج من حيث اللزوجة (Stickiness) كان مرضياً لكل المسافات تحت الاختبار. أفضت الدراسة إلى أن المسافات البينية المتقاربة أدت إلى زيادة الإنتاج مع جودة نوعية المنتج للقطن. عليه نوصى بزراعة صنف القطن البرازيلى (LL) بمسافة 10 سم بين النباتات ليعطي أعلى إنتاجية ونوعية من القطن.